La visita Pastoral del obispo Benito Lué a Corrientes, Río de la Plata, a principios del siglo XIX (Res Gesta, 2018)
In this work we propose to investigate some aspects of the pastoral visits of the bishops to the cities and towns of their dioceses at the beginning of the 19th century. They are valuable documents that provide interesting information about the Church's view of the religious practices of its inhabitants. In this specific case, we will focus on the visit of Bishop Benito Lué y Riega made between 1804 and 1806 to Corrientes, both to the city and to the towns of its episcopal jurisdiction.We are interested in pointing out in the bishop's vision about the behavior of Corrientes parishioners as well as in the reforms that he proposes based on the observations he makes in this marginal territory with respect to other cities. The case study is relevant because it highlights practices and customs rooted in this space that result from a cultural assemblage based on the presence of Guaraní, among other characteristics.
Keywords: Church; Visit; Bishop; 19 century; Corrientes